Phylogeny and evolution - Marín, Walter A. (Universidad de Costa Rica, 2016)
A particular human drive is to arrange things into categories, look for patterns and allocate labels. Since ancient times, humans have applied this to life itself. Today we use the Linnaeus' system of classifi- cation, first published in 1735, which classifies living organisms by grouping them with the most similar visible characteristics into groups.